Comparative genomic analysis of ESBL-producing Escherichia coli from faecal carriage and febrile urinary tract infection in children: a prospective multicentre study. Issue 3 (21st May 2022) - Bidet, Philippe; Birgy, André; Ouldali, Naim; Béchet, Stéphane; Levy, Corinne; Madhi, Fouad; Sobral, Elsa; Cohen, Robert; Bonacorsi, Stéphane
Abstract: Background: The reliability of ESBL-producing Escherichia coli (ESBL-Ec) faecal carriage monitoring to guide probabilistic treatment of febrile urinary tract infection (FUTI) in children remains unclear. Objectives: To compare the genomic characteristics of ESBL-Ec isolates from faecal carriage and FUTI to assess their correlation and identify a FUTI-associated virulence profile. Methods: We conducted a prospective multicentre hospital and ambulatory-based study. We analysed the genotypes and virulence factors of both faecal and FUTI ESBL-Ec by whole genome sequencing. Correlations were assessed by non-parametric Spearman coefficient and virulence factors were assessed by chi-squared tests with Bonferroni correction. Results: We included 218 ESBL-Ec causing FUTI and 154 ESBL-Ec faecal carriage isolates. The most frequent ST was ST131 (44%) in both collections. We found high correlation between carriage and ESBL-Ec FUTI regarding genes/alleles (rho = 0.88, P  < 0.0001) and combinations of virulence genes, MLST and serotypes (rho = 0.90, P  < 0.0001, rho = 0.99, P  = 0.0003, rho = 0.97, P  = 0.005 respectively). Beside this strong correlation, we found five genes that were significantly associated with FUTI ( papC, papGII, hlyC, hek and traJ ). The strongest association with FUTI was found with adhesin gene allele papGII (54% in FUTI versus 16% in carriage) and for papGII and gene traJ alone or in combination (63% versus 24%). Conclusions: The genomic profile of ESBL-Ec causing FUTI in children strongly correlates with faecal carriage isolates except for a few genes. The presence of papGII and/or traJ in a previously identified carriage strain could be used as a marker of uropathogenicity and may guide the empirical antimicrobial choice in subsequent FUTI.